Association Rule Mining Using k-Map Model in Data Mining - Abdullah, Daban Abdulsalam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
In data mining, many algorithms were suggested to define the frequent rules within the data set. One of the problems is to choose a correct algorithm for the problem and the determination of the efficiency of the algorithm has important role during the investigation of hidden knowledge. The thesis describes how to handle data set with Association Rules Analysis/ Market Basket Analysis with the popular Apriori algorithm and k -Map algorithm of data mining. The goal of this thesis is to find the most frequent patterns within the data set and then using different measurements to do further investigation on the obtained frequent patterns. Keywords: Data Mining, Association Rules Analysis, Market-Basket Analysis

ÖZ; Veri madenciliğinde, anlamlı kurallar tanımlamak için bir çok algoritma önerilmiştir. Doğru algoritmayı seçmek ve algoritmanın kullanırlığının kararı verinin içindeki gizli bilginin bulunması için önemli problemlerdir. Bu tez verinin Birliktelik Kuralları Analizinde sıklıkla kullanılan Apriori algoritması ve k-Harita (Karnaugh Haritası) algoritmasının nasıl kullanılacağını tanımlar. Bu tezin amacı verinin içindeki anlamlı kuralları bulmak ve sonrasında ise farklı ölçüler kullanıp anlamlı kurallar için ileri analizler yapmaktır. Anahtar kelimeler: Veri Madenciliği, Birliktelik Kuralları Analizi, Sepet Analizi
Master of Science in Applied Mathematics and Computer Science. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2015. Supervisor: Assist. Prof. Dr. Ersin Kuset Bodur.
Keywords: Mathematics; Applied Mathematics and Computer Science; Data Mining; Association Rules Analysis; Market-Basket Analysis